Star islamiat (compulsory) class 9 new edition federal board - Sajjad muhammad (Star book Lahore, 2023)
The "Star Islamiat" book for the Federal Board is a comprehensive guide aimed at helping students understand and excel in Islamic Studies as per the FBISE curriculum. The book covers a wide range of topics including the Quran, Hadith, Islamic history, and teachings of Islam, ensuring students are well-prepared for their exams. It provides clear and concise explanations of complex concepts in simple language, making it accessible for all students. The book includes various practice questions such as multiple-choice questions, short questions, and long essays to reinforce learning. Additionally, model papers and past exam papers are included to familiarize students with the exam pattern. By aligning closely with the syllabus, the "Star Islamiat" book offers an effective tool for both understanding Islamic principles and performing well in exams.
Keywords: Islam